2018
DOI: 10.18552/ijpblhsc.v6i2.405
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Ethics Education with Health Profession Students Before, During, and After Placements

Abstract: Health professionals must practice ethically in order to ensure compassionate and effective client care; function as good interdisciplinary team members; and protect themselves from litigation, and conduct and ethics complaints. Ethics education is a routine inclusion in health profession degrees, but may only be taught in the classroom, divorced from practice. This article argues that students need ethics education before, during, and after practice placements. We suggest that many powerful opportunities for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
4
0
5
Order By: Relevance
“…Bu tür yaklaşımlar, kritik olayları çözmeye daha az odaklanırken, bir düşünme ve davranış biçimi olarak etik değerleri, ilkeleri ve görevleri korumaya daha fazla odaklanır. Pollard et al (2018) tarafından yapılan yakın tarihli bir inceleme, eğitimcilerin ve öğrencilerin mesleki uygulamaları sırasında etiğe odaklanarak akademik ve uygulama ortamları arasındaki boşluğu doldurabileceğini göstermiştir. Pollard ve meslektaşları, etik eğitimi için karşılanmamış bir fırsatı tanımlayarak, denetleyici etkileşimler sırasında etiğin nadiren tartışıldığını bulmuşlardır.…”
Section: Sağlık Yönetiminde Etiğin öğRetilmesiunclassified

Eğitimde Etik Konular

Çolak,
Akaydın,
Eryılmaz Ballı
et al. 2024
“…Bu tür yaklaşımlar, kritik olayları çözmeye daha az odaklanırken, bir düşünme ve davranış biçimi olarak etik değerleri, ilkeleri ve görevleri korumaya daha fazla odaklanır. Pollard et al (2018) tarafından yapılan yakın tarihli bir inceleme, eğitimcilerin ve öğrencilerin mesleki uygulamaları sırasında etiğe odaklanarak akademik ve uygulama ortamları arasındaki boşluğu doldurabileceğini göstermiştir. Pollard ve meslektaşları, etik eğitimi için karşılanmamış bir fırsatı tanımlayarak, denetleyici etkileşimler sırasında etiğin nadiren tartışıldığını bulmuşlardır.…”
Section: Sağlık Yönetiminde Etiğin öğRetilmesiunclassified

Eğitimde Etik Konular

Çolak,
Akaydın,
Eryılmaz Ballı
et al. 2024
“…A recent review by Pollard et al (2018) showed educators may bridge the gap between academic and practice settings by focussing on ethics during students' professional practica. All health professions students participate in external practica where they apply theoretical knowledge in practice settings; a learning context well suited to fostering ethical sensitivity and reasoning skills.…”
Section: Approaches To Ethics Educationmentioning
confidence: 99%
“…Current best practice in ethics education draws upon experiential learning approaches, including problem-, case-and reflective practice-based curricula (Donaldson, Fistein, andDunn 2010, Numminen, van der Arend, andLeino-Kilpi 2009). Recent innovations include flipped classroom activities, simulation and audience response systems (Pollard et al 2018). Quality ethics learning outcomes may be facilitated by implementation of empirically based ethics cases (Bushby et al 2015), with a case mix that addresses critical incidents and ethics in 'every day' professional practice (Liaschenko, Oguz, and Brunnquell 2006).…”
Section: Best Practice In Ethics Educationmentioning
confidence: 99%
“…A recent review by Pollard et al (2018) identified a significant gap in ethics education for the health professions, namely, opportunities for integrating ethical theory and practice during professional placements. The authors suggested students' ethical reasoning skills may benefit from case-based, interactive learning experiences before professional placements followed by opportunities for critical ethical reflection following placements (Boud, Keough, andWalker 1985, Dunn andMusolino 2011).…”
Section: Best Practice In Ethics Educationmentioning
confidence: 99%
See 1 more Smart Citation